Cosmic Expansion Under Augmented Newtonian Dynamics: A Critical Theoretical Examination - Yadav, Meenakshi (Journal of Educational Research and Policies, 2026)
The standard model of cosmology claims that the Universe is expanding, driven by events arising out of the Big Bang. However, direct evidence for expansion faster than the Hubble shift (i.e. sub-luminal expansion) is lacking on local scales, and the assumption that the CMB is a relic of a hot origin is unnecessary. By applying Wien’s law to present-day cosmic conditions-namely, a Universe almost entirely empty, with a density of one particle per cubic meter - the observed 2.7 K temperature of the CMB emerges naturally, without invoking relic radiation. This paper argues that the CMB reflects present conditions, not ancient ones, and that cosmic expansion, if real, should be observable everywhere, not only at inaccessible distances. These considerations call for a fundamental re-evaluation of current cosmological assumptions.